Odpowiedzi

2010-03-29T22:35:41+02:00
3(2x+3)-5(3y-2)=22
x-3y/4x-7y=-1/*4x-7y

6x+9-15y+10=22
x-3y=-4x+7y/+3y

6x-15y+19=22/-19
x=-4x+10y/+4y

6x-15y=3
5x=10y/:5

6x-15y=3
x=2y

6*2y-15y=3
x=2y

12y-15y=3
x=2y

-3y=3/:(-3)
x=2y

y=-1
x=2*(-1)

x=-2
y=-1

2010-03-29T22:46:22+02:00
3(2x+3)-5(3y-2)=22
x-3y/4x-7y=-1

6x+9-15y+10=22
x-3y/4x-7y=-1

6x-15y=22-10+9
x-3y/4x-7y=-1

6x-15y=3
x-3y/4x-7y=-1/*4x-7y

6x-15y=3
x=-4x+7y+3y

6x-15y=3
5x=10y/:5

6x-15y=3
x=2y

6*2y-15y=3
x=2y

12y-15y=3
x=2y

-3y=3/:(-3)
x=2y

y=-1
x=2*(-1)

y=-1
x=-2

Wydaje mi się, że dobrze odczytałam zadanie ( nie do końca byłam pewna jak dzielić przykład " x-3y/4x-7y = -1 "